2012
DOI: 10.1002/bdrc.21016
|View full text |Cite
|
Sign up to set email alerts
|

Elastin signaling in wound repair

Abstract: Skin is an important organ to the human body as it functions as an interface between the body and environment. Cutaneous injury elicits a complex wound healing process, which is an orchestration of cells, matrix components, and signaling factors that re-establishes the barrier function of skin. In adults, an unavoidable consequence of wound healing is scar formation. However, in early fetal development, wound healing is scarless. This phenomenon is characterized by an attenuated inflammatory response, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 92 publications
2
135
0
Order By: Relevance
“…In this regard, it has been recently reported that the amount of elastin correlates with scarless healing [81]. Indeed, elastin provides skin resistance, matrix synthesis, and supports a range of cell activities, including cell migration and proliferation [81]. Therefore, the presence and organization of elastin is a desirable trait in wound-healing evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been recently reported that the amount of elastin correlates with scarless healing [81]. Indeed, elastin provides skin resistance, matrix synthesis, and supports a range of cell activities, including cell migration and proliferation [81]. Therefore, the presence and organization of elastin is a desirable trait in wound-healing evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Elastin is the important component of the skin, responsible to maintain the mechanical and cell interactive properties. It induces a widerange of cellular activities such as cell migration and proliferation, matrix synthesis, and protease production [38]. Due to these inherent properties of elastin it enhances the process of wound healing.…”
Section: Elastinmentioning
confidence: 99%
“…Elastin is the important component of the skin that maintain the mechanical and cell interactive properties. It induce a wide-range of cellular activities such as cell migration and proliferation, matrix synthesis, and protease production [38]. Elastin enhanced the process of wound healing due to its inherent properties.…”
Section: Elastinmentioning
confidence: 99%